भारतीय दर्शनेषु मोक्ष प्रक्रिया - Swati Kapil (Dr. Chinmay Pandya, 2019)
सारांश - मोक्ष मानव जीवन का परम लक्ष्य है, इसलिये मानव के आदि संविधान वेद से लेकर आज तक सभी धर्म शास्त्रीय ग्रन्थों में मोक्ष का चिन्तन प्राप्त होता है। मोक्ष को मुक्ति, कैवल्य, निःश्रोयस, निर्वाण, अमृत और अपवर्ग आदि नामों से जाना जाता है। विश्व में दो प्रकार की प्रवृत्ति सर्वत्र दृष्टिगोचर होती है प्रथम दुखों को दूर करने की तथा द्वितीय सुखो को प्राप्त करने प्रवृत्ति। दुःख निवृत्ति भी दो प्रकार की है- प्रथम वर्तमान दुःख की निवृत्ति तथा द्वितीय भावी दुःख की निवृत्ति। इन दोनों प्रकार की प्रवृत्तियाँ ही मोक्ष की विचारधारा की जनक कहलाती है। यह धारणा कि हमें अतिशय सुख प्राप्त हो और दुःखो की निवृत्ति हो वेदों के कारण से ही प्राप्त होती है। भारतीय दर्शन में इस अविद्याकृत प्रपंच से मुक्ति प्राप्त करना ही मोक्ष है। वस्तुतः जीवन में त्याग प्रतिष्ठा का नाम ही मोक्ष है। वासना, तृष्णा, अहंता रूपी बंधनों से मुक्ति प्राप्त कर आत्म तत्व की और उन्मुख होना ही मोक्ष है। मन पर अधिकार प्राप्त कर लिया जाये और अहंकार तथा इच्छाओं को जड़ कर दिया जाये तो स्थायी परम आनंद की अनुभूति संभव है। Summary - Moksha is the ultimate goal of human life, that is why the contemplation over moksha is found from the beginning of the human constitution Vedas to all the theological texts till today. Moksha is known by the names Mukti, Kaivalya, Nishroyas, Nirvana, Amrit and Apavarga etc. Two types of tendencies can be found everywhere in the world. First, the tendency to resolve sorrows and secondly, the tendency to attain happiness. Liberation from grievances is also of two types - first, the termination of present sorrow and second, the elimination of future sorrow. Both these tendencies are known for the creation of the ideology of salvation. The belief that we get immense happiness and freedom from sorrows comes only due to the Vedas. In Indian philosophy, freedom from this unseen delusion. In fact, the name of renunciation in life is salvation. Attaining freedom from the chains of desire, greed and ego and aiming for self essence is salvation. By controlling the mind and rooting out the ego and desires, the experience of permanent ultimate joy is possible.